IDENTIFIKASI PERMASALAHAN DALAM MENYIMAK BAHASA JEPANG TERKAIT DENGAN BENTUK PILIHAN JAWABAN SOAL YANG DIALAMI MAHASISWA DI BALI - Desak Made Sri Mardani (Universitas Diponegoro, 2015)
This study aims at investigating the problems in listening test encountered by students of Japanese department in Bali associated with the answer choice of the test. This study was design descriptively in which the subject were 133 Japanese department student of 3rd semester from 3 different universities. The object of this study is the problems encountered by students of Japanese department in Bali associated with the answer choice of the listening test. The result of study showed that the students were easier to answer the test correctly with written form of answer choice. In each main question, it could be seen that the student were easier to find out the answer of ‘fast response’ question than the other main questions. From the analysis of items difficulty it was found that the problems encountered by students in listening were more on items with written answer choice, with different characteristics of the questions.